(3ebGdI aj eYQaI GdCTNGU GdbGFeI hCYeOI GdLHGd hGQJaGY GdZjhes - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3faQV Gf nCnH GQJaGY LHd Gh TNU hfQjO Gf fYdeg afbje TNUG Ydi hLg GdGQV eKd nO gn` s
(3BNQgG (B:s
(3hjfbSe Ydi eG Hjf GdXdjf GdGabjf JMUd ebOGQ GdTNU GdeWdhH GQJaGYg s
(3HgG Tcd gfOSis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(2772) s
Keywords: (3Gdadcs